A new species of Asiopsocus from Puebla, Mexico (Psocoptera: Asiopsocidae) - García Aldrete, Alfonso Neri; Arturo Casasola, José (Instituto de Ecología, A.C., 1995)
The new species Asiopsocus tehuacanus is described and illustrated. It is the fourth species known in the genus, it differs from the other three in genitalic details of both sexes. It is the second species of Asiopsocus recorded in México.